Inversely symmetric interpolatory quadrature rules - De Andrade, E. X. L. [UNESP]; Bracciali, Cleonice Fátima [UNESP]; Sri Ranga, A. [UNESP] (Springer Nature, 2000)
We consider interpolatory quadrature rules with nodes and weights satisfying symmetric properties in terms of the division operator. Information concerning these quadrature rules is obtained using a transformation that exists between these rules and classical symmetric interpolatory quadrature rules. In particular, we study those interpolatory quadrature rules with two fixed nodes. We obtain specific examples of such quadrature rules.
Keywords: Orthogonal Laurent polynomials; Orthogonal polynomials; Quadrature rules; Symmetric distributions